Penyuluhan Hukum tentang Pembuktian dalam Hukum Perdata di Desa Matang Seping Kecamatan Banda Mulia - Suriyani, Meta; Anwar, Saiful; Rusli, Rusli; Elisdawati, Yuni (Pencerah, 2025)
The activities of the Matang Seping Village community, Banda Mulia District, Aceh Aceh Tamiang Regency ,when carrying out civil acts such as borrowing, renting, pawning, debts, buying and selling, waqf, or other cooperation are carried out verbally, often without witnesses to witness it. The community does not understand that letters and witnesses can clarify the problems that occur and provide evidence to resolve problems, either through customary court procedures or district courts. The partner group comes from the community. This community service activity is carried out by providing legal counseling on evidence in civil law to the community so that they prepare and use evidence in accordance with applicable law. The evidence recognized in civil cases consists of written evidence, witness evidence, suspicions, confessions, and oaths. The absence of evidence or weak evidence from the consequences of civil law acts will cause losses to one party. In addition, electronic evidence such as voice recordings, photos, videos, voice notes, or emails can also be used as evidence in court.